(untitled) (Bangladesh Journal of Agricultural Research, 2010)
A two years’ field trial was conducted to evaluate the effect of poultry litter (PL) incorporation of different ages on the yield, nutrient uptake and nutrient balance in Boro rice at BRRI experimental farm, Gazipur (AEZ-28 and land type-High Land) during 2004-05 and 2005-06 Boro seasons. Eight treatment combinations with different aged PL and chemical fertilizers along with a control treatment (no fertilizer) were tested. The treatment combinations were 0, 30, 60, 90, and 120 days’ aged poultry litter, farmers’ 135 days aged poultry litter and 50% of soil test based (STB) chemical fertilizers. All PL treatments received poultry litter 3 t/ha and 50% of STB chemical fertilizers. In both years, 30 days old PL produced significantly higher rice yield with higher nutrient uptake. Keywords: Poultry litter; aging; grain yield; nutrient balance. DOI: 10.3329/bjar.v35i3.6456 Bangladesh J. Agril. Res. 35(3) : 497-505